2007
DOI: 10.1002/mrm.21253
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 13carbon metabolic imaging at 3T with hyperpolarized 13C‐1‐pyruvate

Abstract: We present for the first time dynamic spectra and spectroscopic images acquired in normal rats at 3T following the injection of 13 C-1-pyruvate that was hyperpolarized by the dynamic nuclear polarization (DNP) method. Spectroscopic sampling was optimized for signal-to-noise ratio (SNR) and for spectral resolution of 13 C-1-pyruvate and its metabolic products 13 C-1-alanine, 13 C-1-lactate, and 13 C-bicarbonate. Dynamic spectra in rats were collected with a temporal resolution of 3 s from a 90-mm axial slab usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
246
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(254 citation statements)
references
References 12 publications
8
246
0
Order By: Relevance
“…All animal studies were carried out under a protocol approved by the Institutional Animal Care and Use Committee. A more detailed description of the polarization and animal care procedures can be found in [4][5].…”
Section: Mousementioning
confidence: 99%
See 1 more Smart Citation
“…All animal studies were carried out under a protocol approved by the Institutional Animal Care and Use Committee. A more detailed description of the polarization and animal care procedures can be found in [4][5].…”
Section: Mousementioning
confidence: 99%
“…With the development of techniques to maintain hyperpolarization of carbon-13 in liquid state [1], it has become possible to use 13 C substrates (tracers) for medical imaging [2]. More recent studies have used the metabolically active substrate [l- 13 C]pyruvate to examine its conversion to [l- 13 C]lactate, [l- 13 C]alanine, and 13 C-bicarbonate [3][4][5]. Spectroscopic examination of these metabolic pathways in the presence and absence of disease has enormous diagnostic potential.…”
Section: Introductionmentioning
confidence: 99%
“…The RF coil used in these experiments was a dual-tuned 1 H-13 C coil with a quadrature 13 C channel and linear 1 H channel constructed based on an earlier design (7) and used in prior hyperpolarized 13 C pyruvate studies (3)(4)(5). The inner coil diameter was 8 cm and the length of the coil was 9 cm to accommodate rats of varying size.…”
Section: Mri Mrs and Mrsi Studiesmentioning
confidence: 99%
“…This development has enabled in vivo 13 C MR studies at high signal to noise ratio (SNR) following injection of pre-polarized 13 C substrates (2). It has been shown by using [l-13 C]pyruvate as the substrate for hyperpolarized 13 C MRS/MRSI experiment, real time cellular metabolism can be studied in normal and diseased tissues in vivo (3)(4)(5). These studies have shown the ability to detect the metabolic conversion of the hyperpolarized [l-13 C]pyruvate into [l-13 C]lactate, [l-13 C]alanine and 13 C-bicarbonate after in vivo injection in animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation